Aperiodic bragg reflectors for tunable high-purity structural color based on phase change material - Jana, Sambhu (2024)
Tunable thin-film coating-based reflective color displays have versatile applications including image sensors, camouflage devices, spatial light modulators, and intelligent windows. However, generating high-purity colors using such coatings have posed a challenge. Here, we reveal high-purity color generation using an ultralow-loss phase change material (Sb2S3)-based tunable aperiodic distributed Bragg reflector (A-DBR). By strategically adjusting the periodicity of the adjacent layers of A-DBRs, we realize a narrow photonic bandgap with high reflectivity to generate high-purity orange and yellow colors. In particular, we demonstrate an A-DBR with a large photonic bandgap tunability by changing the structural phase of Sb2S3 layers from amorphous to crystalline. Moreover, we experimentally tailor multistate tunable colors through external optical stimuli. Unlike conventional nano thin-film coatings, our proposed approach offers an irradiance-free, narrowband, and highly reflective color band, achieving exceptional color purity by effectively suppressing reflections in off-color bands.